2015
DOI: 10.1002/jat.3202
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell‐mediated exacerbation of methimazole‐induced acute liver injury in rats

Abstract: Methimazole (MTZ), an anti-thyroid drug, is known to cause liver injury in humans. It has been demonstrated that MTZ-induced liver injury in Balb/c mice is accompanied by T helper (Th) 2 cytokine-mediated immune responses; however, there is little evidence for immune responses associated with MTZ-induced liver injury in rats. To investigate species differences in MTZ-induced liver injury, we administered MTZ with a glutathione biosynthesis inhibitor, L-buthionine-S,R-sulfoximine (BSO), to F344 rats and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Previous studies have indicated that the changes in TLR4, ERK, PPAR-γ signaling were regulated by CYPs, and were related to liver injury ( 17 21 ). Therefore, the relative mRNA expression levels of TLR4, ERK and PPAR-γ were evaluated by RT-qPCR following isoniazid exposure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the changes in TLR4, ERK, PPAR-γ signaling were regulated by CYPs, and were related to liver injury ( 17 21 ). Therefore, the relative mRNA expression levels of TLR4, ERK and PPAR-γ were evaluated by RT-qPCR following isoniazid exposure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in toll-like receptor (TLR)-4 mRNA expression and its signaling pathway were observed in liver injuries induced by acetaminophen, floxacillin, methimazole, lipopolysaccharide and alcohol ( 17 ). TLR4 has been reported to serve an important role in drug-induced liver injury, and TLR4 signal transduction cascades may be related to the cause of these diseases ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…(155) D-galactosamine increases HMGB1 release into plasma, correlating with a decrease in nuclear expression in rat liver (156) ; and, an HMGB1 neutralizing antibody suppressed plasma HMGB1 and inflammatory cytokines and improved liver injury and survival. (156) Methimazole increased plasma HMGB1 3-6 hours after exposure (157) ; this was ameliorated when Kupffer cell activation was blocked, suggesting that HMGB1 may be involved in mediating DILI by Kupffer cells. Rats treated with diclofenac had increased HMGB1 in plasma, (158) and sulfamethoxazole and flucloxacillin stimulated HMGB1 release from human hepatocytes along with markers of cell death and inflammation.…”
Section: Other Hepatotoxinsmentioning
confidence: 99%
“…In vivo studies have shown that BSO pretreatment could enhance DILI caused by carbamazepine (Iida et al, ), methimazole (Akai et al, ) and phenytoin (Sasaki et al, ). However, in the studies presented here, the exacerbation of oxidative stress by the depletion of GSH showed an opposing role that reduced liver damage was caused by TGZ administration (Figure C).…”
Section: Discussionmentioning
confidence: 99%